Physicochemical Characteristics of Yangko Cakes Substituty Glutinous Rice Flour and Kidney Bean Flour (Phaseolus vulgaris L.) with Variations of Cinnamon Extract (Cinnamomum burmanii): Karakteristik Fisikiokimia Kue Yangko Substitusi Tepung Ketan dan Tepung Kacang Merah (Phaseolus vulgaris L.) dengan Variasi Ekstrak Kayu Manis (Cinnamomum burmanii) - Retna Indri Juwita; Vivi Nuraini; Merkuria Karyantina (Fakultas Sains dan Teknologi Unisri, 2024)
Yangko cake is a semi-wet food made from glutinous rice flour with the addition of a sugar solution. In order to improve the characteristics of the yangko cake, an ingredient is added, namely kidney bean flour and cinnamon extract. Kidney beans are one type of legume that has a high protein source so it can add nutritional value to food products. Kidney bean has an unpleasant taste, therefore it needs to be balanced with the addition of cinnamon extract, which is expected to reduce the unpleasant flavor of the yangko cake which consumers preferred. The experimental design used is a CRD, with the first factor being the ratio of glutinous rice flour and kidney bean flour with a ratio of 90:10, 80:20, and 70:30. The addition of cinnamon extract in various amounts (2 ml, 4 ml, and 6 ml) was the second element. The inclusion of substitute glutinous rice flour and kidney bean flour, coupled with the variation of cinnamon extract produced yangko cake with 3,80% fiber content and 5,76% protein content. Chemically, physically and organoleptically, the best product from several formulations of the yangko cake was with 70:30 of glutinous rice flour to kidney bean flour and 6 ml of cinnamon extract, with 47.98% water content, 0.66% as content, 31,36% total sugar content and with a hardness of 28.82 N, a gumminess of 4.92 N, a chewiness of 2.28 N then a cohesiveness of 0.64 Ns. The organoleptic characteristic of the yangko cake was the most preferred by the panelists, with a value of 3,76 (preferred). The yangko cake substitusion of glutinous rice flour and kidney beans with the addition of cinnamon extract is a food ingredient that has quite high protein and fiber.